Improved photocatalytic activity of nanocrystalline ZnO by coupling with CuO. (July 2017) - Xu, Linhua; Zhou, Yang; Wu, Zijun; Zheng, Gaige; He, Jiaojiao; Zhou, Yanjing
Abstract: Although ZnO as a photocatalyst has attracted wide attention in the word in recent years, it is still a big challenge to develop low-cost, visible-light responsive ZnO based photocatalysts which can be used on a large scale. In this work, the CuO/ZnO nanocomposites have been synthesized by a facile one-step hydrothermal method and the influence of CuO contents on the photocatalytic properties of the nanocomposites has been investigated. The crystalline phase of the CuO/ZnO nanocomposites is determined by X-ray diffraction (XRD); the morphology and microstructures of the samples are analyzed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The photocatalytic performance of the samples is tested using methylene blue （MB）dyes as the simulated pollutant under irradiation of a Xe lamp. Compared with pure ZnO, the photocatalytic activity of the CuO/ZnO nanocomposites is largely improved, especially for the sample prepared by the precursor solution with the molar ratio of Zn 2+ : Cu 2+ =2:1. The improvement of the photocatalytic activity is attributed to two main factors: (1) the band coupling improves the separation efficiency of photogenerated electrons and holes; (2) the utilization efficiency for solar energy is enhanced in the CuO/ZnO coupling system. Graphical abstract: The formation of CuO-ZnO heterojunction leads to a large decrease of photoluminescence compared with pure ZnO powders, which is favorable for photocatalytic applications. Highlights: CuO/ZnO nanocomposites were synthesized by a facile one-step hydrothermal method. The photocatalytic performance of the CuO/ZnO nanocomposites is largely improved. The improved photocatalytic performance is attributed to the band coupling. CuO contents have a great influence on the photocatalytic performance.